Social Distance, Connectedness, and Product Familiarity on Endorsement Evaluations: An Experimental Approach - Centeno, Dave DG (Philippine Management Review; Vol 25 (2018), 2019)
Contrary to previous research on social distance suggesting that widened social distance is linked to power, this paper argues that indeed narrowing social distance creates increased favorable evaluations in the context of endorsements. By experimentally framing the source such as celebrity endorsers into a close relationship social category (e.g., ‘friend’, ‘family’), product attitudes and purchase intentions increase. This effect was mediated by connectedness and was moderated by the familiarity of consumers towards the product. The research context is in the Philippines where celebrity culture is predominantly relational due to its highly collectivistic culture. Implications on close relationship and relational paradigm in celebrity endorsements are discussed.